NGHIÊN CỨU SỬ DỤNG CO2 TỪ KHÍ THẢI ĐỐT THAN ĐỂ NUÔI VI TẢO SPIRULINA PLATENSIS - Kim, Đặng Đình; Tựa, Trần Văn; Cư, Nguyễn Tiến; Anh, Đỗ Tuấn; Thơm, Đặng Thị; Kiên, Hoàng Trung; Thủy, Lê Thu; Nguyệt, Vũ Thị; Chính, Mai Trọng; Vượng, Nguyễn Văn (Vietnam Journal of Science and Technology, 2012)
UTILIZATION OF CO2 CAPTURED FROM THE COAL-FIRED FLUE GAS FOR GROWING SPIRULINA PLATENSIS SP4 The paper presents the results concerning the utilization of CO2 captured from the coal-fired flue gas for growing the Spirulina platensis SP4 in laboratory condition. Several research results on the conversion of CO32- and HCO3- in algal suspension and CO2 intake efficiency by the alga were presented. The growth and biomass quality of Spirulina platensis SP4 using CO2 from fired-coal flue gas were equivalent to that of the alga grown in the pure CO2 experimental lot.